Educação em Roraima: institucionalização escolar de 1943 a 2001 - Siems-Marcondes, Maria Edith Romano (Revista de História e Historiografia da Educação, 2017)
Este texto apresenta aspectos da trajetória histórica de institucionalização escolar ocorrida em Roraima do período de 1943, quando o Território Federal é implantado, até 2001, quando se consolida a primeira década de instalação do Estado de Roraima. Trata-se de uma análise documental em que apresentamos registros oficiais de criação de unidades escolares e sistematizamos dados de pesquisas anteriores. Na análise dos processos de constituição histórica da educação escolar em Roraima, identificamos que sua estruturação acompanha as políticas estabelecidas para a região, interligada às políticas expansionistas e de ocupação. Education in Roraima: school institutionalization from 1943 to 2001. This text presents aspects of the historical trajectory of school institutionalization that occurred in Roraima in the period of 1943, when the Federal Territory was implemented until 2001, when the first decade of the State of Roraima was consolidated. It is a documentary analysis in which we present official records of the creation of school units and systematize data from previous researches. In the analysis of the processes of historical constitution of school education in Roraima, we identified that its structuring accompanies the policies established for the region, linked to expansionist and occupation policies. Keywords: History of Education; Expansion of schooling; History of Brazilian education.